The Interactions between Two Fungal Endophytes Epicoccum layuense R2-21 and Alternaria alternata XHYN2 and Grapevines (Vitis vinifera) with De Novo Established Symbionts under Aseptic Conditions - Pan, Xiao-Xia; Liu, Hui-Zhi; Li, Yu; Zhou, Ping; Wen, Yun; Lu, Chun-Xi; Zhu, You-Yong; Yang, Ming-Zhi (Journal of fungi (Basel), 2023)
In this study, we focused on grapevine–endophyte interactions and reprogrammed secondary metabolism in the host plant due to defense against the colonization of endophytes. Thus, the transcriptional responses of tissue cultured grapevine seedlings (Vitis vinifera L. cv.: Cabernet Sauvignon) to two fungal endophytes Epicoccum layuense R2-21 (Epi R2-21) and Alternaria alternata XHYN2 (Alt XHYN2) at three different time points (6 h, 6 d, 15 d) were analyzed. As expected, a total of 5748 and 5817 differentially expressed genes (DEGs) were separately initiated in Epi R2-21 and Alt XHYN2 symbiotic tissue cultured seedlings compared to no endophyte treatment. The up-regulated DEGs at all time points in Epi R2-21- or Alt XHYN2–treated seedlings were mainly enriched in the flavonoid biosynthesis, phenylpropanoid biosynthesis, phenylalanine metabolism, stilbenoid, diarylheptanoid and gingerol biosynthesis, and circadian rhythm–plant pathways. In addition, the up-regulated DEGs at all sampling times in Alt XHYN2-treated tissue cultured seedlings were enriched in the plant–pathogen interaction pathway, but appeared in Epi R2-21 symbiotic seedlings only after 15 d of treatment. The down-regulated DEGs were not enriched in any KEGG pathways after 6 h inoculation for Epi R2-21 and Alt XHYN2 treatments, but were enriched mainly in photosynthesis–antenna proteins and plant hormone signal transduction pathways at other sampling times. At three different time points, a total of 51 DEGs (all up-regulated, 1.33–10.41-fold) were involved in secondary metabolism, and 22 DEGs (all up-regulated, 1.01–8.40-fold) were involved in defense responses in endophytic fungi symbiotic tissue cultured seedlings. The protein–protein interaction (PPI) network demonstrated that genes encoding CHS (VIT_10s0042g00920, VIT_14s0068g00920, and VIT_16s0100g00910) and the VIT_11s0065g00350 gene encoding CYP73A mediated the defense responses, and might induce more defense-associated metabolites. These results illustrated the activation of stress–associated secondary metabolism in the host grapevine during the establishment of fungi–plant endophytism. This work provides avenues for reshaping the qualities and characteristics of wine grapes utilizing specific endophytes and better understanding plant–microbe interactions.